Enhancing growth, vitality, and aromatic richness: unveiling the dual magic of silicon dioxide and titanium dioxide nanoparticles in Ocimum tenuiflorum L. - Bhat, Urooj Hassan; Uddin, Moin; Chishti, Aman Sobia; Singh, Sangram; Singh, Sarika; Khan, M. Masroor A.; Mukarram, Mohammad (Frontiers in Plant Science, 2024)
Ocimum tenuiflorum, commonly known as "Holy basil," is renowned for its notable medicinal and aromatic attributes. Its unique fragrance attributes to specific volatile phytochemicals, primarily belonging to terpenoid and/or phenylpropanoid classes, found within their essential oils. The use of nanoparticles (NPs) in agriculture has attracted attention among plant researchers. However, the impact of NPs on the modulation of morphophysiological aspects and essential oil production in medicinal plants has received limited attention. Consequently, the present study aimed to explore the effect of silicon dioxide (SiO2) and titanium dioxide (TiO2) nanoparticles at various concentrations (viz., DDW (control), Si50+Ti50, Si100+Ti50, Si100+Ti100, Si200+Ti100, Si100+Ti200 and Si200+Ti200 mg L -1 ) on growth, physiology and essential oil production of O. tenuiflorum at 120 days after planting (DAP). The results demonstrated that the combined application of Si and Ti (Si100+Ti100 mg L -1 ) exhibited the most favourable outcomes compared to the other combinational treatments. This optimal treatment significantly increased the vegetative growth parameters (root length (33.5%), shoot length (39.2%), fresh weight (62.7%) and dry weight (28.5%)), photosynthetic parameters, enzymatic activities (nitrate reductase and carbonic anhydrase), the overall area of PGTs (peltate glandular trichomes) and essential oil content (172.4%) and yield (323.1%), compared to the control plants. Furthermore, the GCMS analysis showed optimal treatment (Si100+Ti100) significantly improved the content (43.3%) and yield (151.3%) of eugenol, the primary active component of the essential oil.This study uncovers a remarkable and optimal combination of SiO2 and TiO2 nanoparticles that effectively enhances the growth, physiology, and essential oil production in Holy basil.These findings offer valuable insights into maximizing the potential benefits of its use in industrial applications.